LOGISTICS TO STRENGTHEN THE COMPETITIVE POSITIONOF COMMERCIAL ENTERPRISES - BEREZIVSKYI, YAROSLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
A significant number of scientific economic theories have been identified, which substantiate the essential characteristics of the technological competitiveness of the national economy. The difference between each of the theories is due to the evolution of economic development, conditions and factors of formation, as well as directions and means (tools) to ensure the technological competitiveness of the national economy. The conditions and factors of formation of technological competitiveness of the national economy according to economic theories of competition – blue ocean, global advance of competitors, competitive advantages, cyclical development of economy, neoliberalism, structuring are allocated. In each of the theories of competition as their historical evolution, the technological competitiveness of the economy was considered in the context of access and ability to effectively use technological resources, the formation of the market of innovation and technology, implementation of state policy to stimulate innovation. Taking into account theories of competition allows to clarify the important characteristics of technological competitiveness of the national economy, which relate to determining the influence of society, state, market environment, globalization and informatization on the creation and implementation of technologies in economic processes, economic competitiveness. Analysis of the evolution of scientific views shows the high intensity of changes in the field of competition and provides a wide range of conditions and factors for the formation of technological competitiveness, the development of economic agents. Accordingly, the lack of opportunities for technological and innovative development of national producers should be regarded as the main threat to the competitiveness of the economy. These are market, infrastructural, technological, innovative, intellectual, resource and other trends, in the context of which it becomes possible to effectively use competitive opportunities.